Do as Some Said, or as Most Did?-A Foucauldian Experiment with Nineteenth-Century HIP - Kennaway, George (Current Musicology, 2011)
Performers and researchers who explore performance practices of the late nineteenth and early twentieth centuries frequently come up against a problem recently highlighted by musicologist Daniel Leech-Wilkinson, among others. Comparing recordings of Schubert’s “An die Musik” from 1911 and 1997, he observes that the contrast between the two is deeply unsettling, and that the “audience to whom one seems just right may find the other a travesty” (Leech – Wilkinson 2011:2). Recordings by performers like Adelina Patti will reliably induce astonished laughter in an unprepared modern audience, and the slow, heavy portamento of early twentieth -century cellists such as Hans Kronold has a similar effect on conservatory cello students. The contrast between then and now is not simply a matter of different but equally valid performing styles, or a question of, e.g., the degree of portamento employed, which a little audience re-education would eventually make familiar. It appears to challenge a modern audience’s very notion of what musical expression is or means. The modern laughter is not derisive. It is provoked by a sudden collision of incongruous performance codes. This paper explores the application of Foucault’s concepts of enonce and discours to musical performance, to the peculiar aspects of older performing styles, and to the reactions they produced in the context of nineteenth century annotated editions of chamber music.3 Historically Informed Performance (hereafter referred to as HIP) is supported and sustained by performers and academic researchers. The research is largely positivist and does not generally engage with issues and methodologies typical of the more theoretical musicology that has emerged in recent decades. Likewise, the “cultural turn” has largely escaped performers. The simple practicalities of performance do not fit well with such notions as the death of the author, the decalage between sign and signified, or representations of the Other. Rehearsals are generally not given over to discussions of hermeneutics versus phenomenology. This paper is a preliminary step in showing how such theoretical approaches could be fruitful for both performance practice and scholarship.